Privação de escolaridade: a situação do jovem em conflito com a lei e a escolarização - FREITAS, Riane Conceição Ferreira (Universidade Federal do Pará, 2021)
This article aims to reveal how are redefined the current educational policies for the young person who committed an offense and is serving a socio-educational and freedomdepriving sentence in a confinement unity. Through documentary research, we analyzed the official reports which reveal the promotion of schooling or non-schooling to these young people in the period serving the measure. Our theoretical and methodological reference is historicaldialectical materialism. Our conclusions indicate that the current model of rehabilitation has little effectiveness for the reintegration of the young person after the confinement period for the fulfillment of socio-educational measures.